RDW, JUMLAH TROMBOSIT DAN RPR DENGAN INDEKS FIB-4 DI HEPATITIS C - Yenny Yulianti; Banundari Rachmawati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2016)
Hepatitis C virus infection is one of the main causes of worldwide chronic liver disease. The determining of fibrosis level in the liverdisease is essential. The red blood cell distribution width (RDW) is a potential prognostic index for liver disease. The platelet (PLT)count has been used as the biomarker for liver fibrosis. RDW to platelet ratio (RPR) is devised to amplify the difference in the RDW andplatelets among patients with different liver fibrosis stages. Fibrosis 4 (FIB-4) indexes are accurate non-invasive methods to predict thelevel of liver fibrosis of HCV-monoinfected patients. The objective of this study is to know the correlation of RDW, PLT count, and RPR withFIB-4 index in hepatitis C patients by analyzing them. The study was carried out observationally with cross sectional approach betweenFebruary−March 2015 at the Dr. Kariadi Hospital, on samples collected consecutively from the medical records of hepatitis C patients.The data processing was performed with Pearson/Spearman correlation. There was a strong positive correlation between RDW and FIB-4index (r=0.624; p=0.000) and between RPR with FIB-4 index (r=0.674; p=0.000), while there was a strong negative correlationbetween PLT count and FIB-4 index (r=-0.600; p=0.000). From this study it can be concluded that there was an increased RDW and RPRresulting in a higher FIB-4 index. There was also found a decreased PLT resulting from higher FIB-4 index .The opinion of the researchersis that further studies for prospective multicentres are needed to be carried out, so that the results can be more generalized.